PENGARUH MINUMAN SODA TERHADAP BSETTING TIME DAN KUAT TEKAN BETON - Panca Rannie Nursa; Kusno Adi Sambowo; Rosmawita Saleh (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2021)
This study aims to examine the change in concrete behavior in regards to adding soda drinks as retarder and to compare the properties of cocrete using soda drinks and concrete without using soda. In this study, the writer uses soda drink content in 3%, 6%, 9%, and 12% variatons based on cement weight. Each variations uses 1 specimen for vicat tests and 2 specimens is used for compressive strength test. In testing using the vicat tool it measures the delay that occurs in content levels of 3%, 6%, 9%, and 12% could be considered retarders, where as compressive testing examines the maximum strength acquired from adding soda to the concrete is increased by 1.64% with a variation of 3% from normal concrete and decreased gradually by 1,9% 3,9%, and 4,11% with variations of 6%, 9%, and 12% respectively